Propuesta de documentación de un sistema de gestión de calidad basado en la Norma ISO 9001:2015 para la empresa CONSTRUNAL DE AGUAS S.A.S (2022)
As time has passed in all companies and industries has seen a very important factor which has been determined as quality this factor has been preliminary for each of them, in which a very good benefit has been seen when implementing a management system